Cheryl Day's treasury of Southern baking - Day, Cheryl (ArtisanBooks, 2021)
"My great-grandmother was both enslaved and a pastry cook who was famous for her biscuits and cakes. There is power in that." -Cheryl Day, in the New York Times. And from this position of strength comes Day's next cookbook: a complete book of Southern baking recipes written by this great-grandchild of a former slave who is also one of our country's most acclaimed bakers. In a tome filled with recipes for both savory and sweet baked goods and pastries, Day shows that the creators of our favorite Southern recipes-from cathead biscuits to chess pie-were the slaves who worked in the kitchens of the grand home and plantations of the South. Today these recipes have become a beloved part of American cuisine, and Day shares the secrets to making all the Southern baking mainstays, like Flaky Buttery Biscuits and Skillet Cornbread, and creative twists, like a Cold-Oven Pound Cake and Sweet Tea Custard, as well as accompaniments and drinks to serve alongside. Organized by category, there are Southern slow breads like Sally Lunn Bread and Buttermilk Buns; coffee cakes and loaf cakes, like a Brown Butter Sock-It-to-Me Cake and a 7-Up Cake; layer cakes, including a Pig-Pickin' Cake that's a mainstay at Southern barbecues; cookies good for Southern teas, like Lime Cornmeal Shortbread; and recipes to illustrate an evolving South, with those from different cultures too-from Mexican Concha Buns to French Madeleines made with cornmeal. Pies are an important part of Southern food, and this book features both classic and unique favorites, including fruit pies, chocolate pies, savory pies, and hand pies, all with an expanded section on piecrust variations. Cakes take the form of sheet cakes, loaf cakes, and layers cakes and include lessons on cake decorating. This monumental piece of work is Cheryl Day baking at its best with recognition of the past and a strong case for why her Southern baking is our future"--